Association of Performing Arts Collections: a resource for theatre research. Issue 1 (2nd January 2016) - Jones, Chris
Abstract: The Association of Performing Arts Collections (APAC) is a professional organisation whose members – archives, libraries, and museums – are responsible for most of the performing arts heritage of the UK and Ireland. The article outlines how APAC can help theatre researchers locate materials using the information and search tools available on the association's website. The article highlights a selection of members' collections relating to Stanislavski, Moscow Art Theatre, theatre history, theatrical productions, and directing.